Time-dependent metabolomics uncover dynamic metabolic adaptions in MCF-7 cells exposed to bisphenol A - Zhao, Haoduo. (2023)
The biochemical consequences induced by xenobiotic stress are featured in dose-response and time-resolved landscapes. Understanding the dynamic process of cellular adaptations is crucial in conducting the risk assessment for chemical exposure. As one of the most phenotype-related omics, metabolome in response to environmental stress can vary from seconds to days. Up to now, very few dynamic metabolomics studies have been conducted to provide time-dependent mechanistic interpretations in understanding xenobiotics-induced cellular adaptations. This study aims to explore the time-resolved metabolite dysregulation manner and dynamically perturbed biological functions in MCF-7 cells exposed to bisphenol A (BPA), a well-known endocrine-disrupting chemical. By sampling at 11 time points from several minutes to hours, thirty seven significantly dysregulated metabolites were identified, ranging from amino acids, fatty acids, carboxylic acids and nucleoside phosphate compounds. The metabolites in different pathways basically showed distinct time-resolved changing patterns, while those within the common class or same pathways showed similar and synchronized dysregulation behaviors. The pathway enrichment analysis suggested that purine metabolism, pyrimidine metabolism, aminoacyl-tRNA biosynthesis as well as glutamine/glutamate (GABA) metabolism pathways were heavily disturbed. As exposure event continued, MCF-7 cells went through multiple sequential metabolic adaptations from cell proliferation to energy metabolism, which indicated an enhancing cellular requirement for elevated energy homeostasis, oxidative stress response and ER-α mediated cell growth. We further focused on the time-dependent metabolite dysregulation behavior in purine and pyrimidine metabolism, and identified the impaired glycolysis and oxidative phosphorylation by redox imbalance. Lastly, we established a restricted cubic spline-based model to fit and predict metabolite’s full range dysregulation cartography, with metabolite’ sensitivity comparisons retrieved and novel biomarkers suggested. Overall, the results indicated that 8 h BPA exposure leaded to global dynamic metabolome adaptions including amino acid, nucleoside and sugar metabolism disorders, and the dysregulated metabolites with interfered pathways at different stages are of significant temporal distinctions.